Computer-based learning in psychology using interactive laboratories - Stephen Richards (Association for Learning Technology, 1994)
Traditional approaches to computer-based learning often focus on the delivery of information. Such applications usually provide large stores of information which can be accessed in a wide variety of ways. Typical access facilities provided within such applications include Boolean search engines and hypermedia (non-linear) browsing. These types of approach often centre on providing human-computer dialogues which are relatively low on interaction. The interactive-laboratory approach, however, aims to limit the quantity of information presented, and instead to provide a highly interactive learning environment. In the field of psychology, users are able interactively to design and deliver a broad range of psychological experiments. This paper details the approach, and describes how it can be used to teach psychology within a university environment. The way in which its effectiveness as a learning tool can be evaluated is also discussed